Lactobacillus acidophilus Improves Intestinal Inflammation in an Acute Colitis Mouse Model by Regulation of Th17 and Treg Cell Balance and Fibrosis Development - Park, Jin-Sil; Choi, JeongWon; Jhun, JooYeon; Kwon, Ji Ye; Lee, Bo-In; Yang, Chul Woo; Park, Sung-Hwan; Cho, Mi-La (Journal of medicinal food, 2018)
Disruption of the balance among the microbiota, epithelial cells, and resident immune cells in the intestine is involved in the pathogenesis of inflammatory bowel disease (IBD). Probiotics exert protective effects against IBD, and probiotic commensal Lactobacillus species are common inhabitants of the natural microbiota, especially in the gut. To investigate the effects of Lactobacillus acidophilus on the development of IBD, L. acidophilus was administered orally in mice with dextran sodium sulfate (DSS)-induced colitis. DSS-induced damage and the therapeutic effect of L. acidophilus were investigated. Treatment with L. acidophilus attenuated the severity of DSS-induced colitis. Specifically, it suppressed proinflammatory cytokines such as interleukin (IL)-6, tumor necrosis factor-α, IL-1β, and IL-17 in the colon tissues, which are produced by T helper (Th) 17 cells. Moreover, in vitro L. acidophilus treatment directly induced T regulatory (Treg) cells and the production of IL-10, whereas the production of IL-17 was suppressed in splenocytes. In addition, we found that L. acidophilus treatment decreased the levels of α-smooth muscle actin, a marker of activated myofibroblasts, and type I collagen compared with control mice. These results suggest that L. acidophilus may be a novel treatment for IBD by modulating the balance between Th17 and Treg cells, as well as fibrosis development.